1979
DOI: 10.1073/pnas.76.12.6132
|View full text |Cite
|
Sign up to set email alerts
|

Electron-nuclear double resonance of the hydrogen peroxide compound of cytochrome c peroxidase: identification of the free radical site with a methionyl cluster.

Abstract: The results of electron-nuclear double resonance and electron paramagnetic resonance (EPR) studies on the hydrogen peroxide compound of yeast cytochrome c peroxidase are inconsistent with previous proposals for the source of the EPR signal in this compound, in particular with its identification with an aromatic amino acid radical such as would arise by oxidation of a tryptophanyl side chain. The present observations lead us to propose that the EPR signal is associated with a cluster containing at least one met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…33 While the intermediate product of cytochrome c peroxidase with substrate contains its two oxidizing equivalents in the form of a ferryl ion and and a free radical of an amino acid in the protein part of the molecule. 34 - 35 Recently, Lambeir et al 36 showed that PGH synthase reacts with organic hydroperoxides and fatty acid hydroperoxides in milliseconds to generate an intermediate which is spectrally similar to compound I of horseradish peroxidase. Compound I of PGH synthase is then converted to compound II within 170 msec.…”
Section: Resultsmentioning
confidence: 99%
“…33 While the intermediate product of cytochrome c peroxidase with substrate contains its two oxidizing equivalents in the form of a ferryl ion and and a free radical of an amino acid in the protein part of the molecule. 34 - 35 Recently, Lambeir et al 36 showed that PGH synthase reacts with organic hydroperoxides and fatty acid hydroperoxides in milliseconds to generate an intermediate which is spectrally similar to compound I of horseradish peroxidase. Compound I of PGH synthase is then converted to compound II within 170 msec.…”
Section: Resultsmentioning
confidence: 99%
“…[11] At about the same time, ENDOR measurements on the CCP ES radical by Brian Hoffman and coworkers were interpreted in terms of a nucleophilically stabilized methionyl radical. [12] The advent of site-directed mutagenesis helped resolve some of the uncertainty surrounding the identity of the CCP ES radical. Dave Goodin, Grant Mauk, and Michael Smith demonstrated that Met 172 could not be the site of this radical, [13] and measurements from Kraut’s laboratory on the CCP Trp 51 Phe mutant demonstrated that this residue was not the source of the radical signal.…”
Section: Free Radicals In Proteinsmentioning
confidence: 99%
“…In contrast, reaction of CCP with hydrogen peroxide produces an oxidized intermediate, compound ES, that is analogous to compound I except that the porphyrin radical cation is absent. Instead, an electron paramagnetic resonance (EPR) signal is observed at g = 2 that is only weakly magnetically coupled to the (Fe4+=O) iron center and this signal has generally been attributed to a free radical residing on a reversibly oxidized protein residue (10)(11)(12). As compound ES is believed to be an intermediate in the catalytic oxidation of ferrocytochrome c by CCP, detailed understanding of this form of the enzyme is of considerable importance.…”
mentioning
confidence: 99%
“…In addition, Trp-51 is replaced by phenylalanine, a less easily oxidized residue, in all other peroxidases and catalase (2). However, Hoffman and coworkers (12,16) have performed an extensive study of the EPR and electron nuclear double resonance (ENDOR) properties of the radical species at liquid helium temperature and have concluded that the data are completely inconsistent with the existence of either a neutral or cationic tryptophan radical. Instead, they proposed that a nucleophilically stabilized sulfur radical was consistent with the intrinsic anisotropy of the EPR signal at 4 K. The most likely candidate for such a center is Met-172, which lies 3.7 A below the proximal heme face (3).…”
mentioning
confidence: 99%